Cost-effectiveness of long-acting reversible contraceptive methods: a review - Moray, Kusum V.; Chaurasia, Himanshu; Joshi, Beena N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Long-acting reversible contraception (LARC) methods are proven to be effective in preventing unintended pregnancies. Evidence on cost-effectiveness of these methods will enable policy makers to introduce them in national policies and programs to improve contraceptive access. The aim was to review the studies based on economic evaluations of LARC methods and provide evidence to policy makers to renew their commitment to family planning access. A review of studies on economic evaluations of LARC methods was done. This article uses data from three electronic databases: PubMed, Cochrane and Web of Science to examine whether LARC is cost-effective for clinical trials. The results are presented as a narrative review and summary tables. The literature search yielded 87 studies and 12 studies (five economic evaluations studies from USA) and (five studies from Europe while two studies were from low and middle-income countries) were included. Out of 12 papers, nine had multiple comparators; seven included female sterilization as a comparator, while two studies compared one individual LARC contraceptive method with an individual SARC method. All studies consistently showed that LARCs dominated all SARC (short acting reversible contraceptives) methods. Within LARC, copper IUD, LNG-IUS and implant were more cost-effective than DMPA. After a period of five years, female sterilization turned out to be more cost-effective than LARC methods. LARC methods are cost-effective as compared to SARC methods, especially after 1 year of use. Vasectomy is more cost-effective than LARC methods. Policy makers can consider the findings of this review to aid decision making in contraceptive method introduction or scale-up access.